Biological control of the native endophytic fungus Pochonia chlamydosporia from the root nodule of Dolichos lablab on Fusarium wilt of banana TR4 - Zhou, Yunfan; Yang, Limei; Xu, Shengtao; Li, Shu; Zeng, Li; Shang, Hui; Li, Xundong; Fan, Huacai; Zheng, Si-Jun (Frontiers in Microbiology, 2024)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense, Tropical Race 4 (TR4) is a soil borne disease, and it is devastating. At present, the biological control using antagonistic microorganisms to mitigate TR4 is one of best strategies as a safe and green way. Yunnan has abundant and diverse microbial resources. Therefore, eighteen native endophytic fungi were isolated from a root nodule sample of Dolichos lablab in the mulch for banana fields in Yuxi, Yunnan Province, China.The YNF2217 strain showed high antagonistic activity against TR4 in plate confrontation experiments, and the inhibition rate of YNF2217 is 77.63%. After TR4 culture with YNF2217 for 7 days in plate confrontation experiments, the morphology of TR4 mycelium deformed and swollen by scanning electron microscopy observation. According to morphological characteristics and sequence analysis, the strain YNF2217 was identified as Pochonia chlamydosporia. In the greenhouse pot experiment, the biocontrol effect of YNF2217 fermentation solution on TR4 was 70.97% and 96.87% on banana plant leaves and corms, respectively. Furthermore, YNF2217 significantly promoted the growth of banana plants, such as plant height, leaf length, width and number, pseudostem girth, fresh weight both in the aboveground and the underground. The dynamics observation of TR4 infestation in banana roots and corms, as well as real-time fluorescence quantitative PCR verified that YNF2217 inoculation could significantly reduce the content of TR4. Therefore, YNF2217 as P. chlamydosporia, which was first time found in China and reported here, is expected to be an important new type fungal resource for the green control of Fusarium wilt of banana in the future.